Comparative cost analysis of Lebanon's hospitality services - Ladki, Said M. (1998)
A study which compares the costs of hospitality services in Lebanon versus its neighbouring tourism rival nations; analyses the causes of such high costs; and offers suggestions leading to a halt in price increase or possibly price reduction strategies is presented. The findings of the study attribute this high price to the following factors: local hospitality operators' pricing strategies; the low priority given to tourism by the Lebanese government; high taxation; lack of pro-tourism development legislation; the imposition of an airport utilization tax; local opportunists pushing up prices; and a limited room supply.